A LEGAL ANALYSIS OF LGBT MARRIAGE EFFORTS WITHIN THE CONTEXT OF PANCASILA (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2026)
The research discusses how Pancasila, as the state philosophy, state ideology, and way of life of the Indonesian people, which was born from acculturation and formulation of the diversity of customs, culture, nobility, religion, and beliefs that already exist and are developing in Indonesia, is faced with LGBT propaganda that uses human rights pretext. Many times, LGBT propaganda has tried to find loopholes and opportunities to be accepted in Indonesian society; they have even tried to get recognition and validation of their marriage. However, until now, LGBT people have not found a space or a place in Indonesia. The aim of this research is to provide understanding to the Indonesian people, especially LGBT people, about the role of Pancasila in preventing them, even though they hide behind international human rights in the name of freedom of expression. This research is library research, where the data comes from writings in the form of books, journals, articles, news, and magazines. From the results of this research, it was found that LGBT people are trying to get a place and space, as well as recognition and validation for what they do. They argue in the name of freedom of expression because LGBT is considered human nature. With Pancasila's analysis of LGBT as the basis of the Republic of Indonesia, especially the first principle of Pancasila, which is "belief in One Almighty God," in the context of LGBT, it is very contrary to Godly values, where all religions that live in Indonesia reject the legality of LGBT in Indonesia. While the second principle of Pancasila is "Just and Civilized Humanity," in the context of LGBT (Lesbian, Gay, Bisexual, and Transgender), the approach to the perspective of the second principle, Pancasila, protects human rights but does not conflict with religious norms, especially Islamic law, as adherents of the majority of Muslims in Indonesia. Because in Islam, something that is considered good by religion is also good in human eyes, while something that is considered bad in human eyes is also bad in religious eyes. Goodness will produce a reward that will take every servant to His heaven; evil will make him angry and take him to hell.